The effects of beetroot powder as a colorant on the color stability and product quality of white compound chocolate and chocolate spread - Baycar, Abdullah; Konar, Nevzat; Goktas, Hamza; Sagdic, Osman; Polat, Derya Genc (SOC BRASILEIRA CIENCIA TECNOLOGIA ALIMENTOS, 2022)
This study determines the possibility of using spread (SC) and compound chocolate (CC) as delivering agents of betalains, bioactive compounds and coloring agents. Therefore, the effects of various beetroot powder concentrations (0.0-1.00 g/100 g) on SC and CC's quality parameters and the associated visual properties over a 12-week period under accelerated shelf-life conditions were investigated. The hardness and plastic viscosity values of CC significantly increased as the amount of beetroot powder increased (P 0.05). The use of beetroot powder for both groups caused a significant decrease in the samples' color values, and the redness associated with the pigment source also significantly increased (p<0.05). The findings revealed that high concentrations of beetroot powder did not significantly impact CC's color stability to the same extent that it impacted the SC's color stability. This study was made as a preliminary study to produce functional foods.
Keywords: confectionery; beetroot; chocolate spread; color stability; functional foods; PARTICLE-SIZE DISTRIBUTION; RHEOLOGICAL PROPERTIES; POTENTIAL APPLICATION; FOOD COLORANTS; MILK CHOCOLATE; BETALAINS; RED; MICROSTRUCTURE; PIGMENTS; TEXTURE; Food Science & Technology